Some considerations of fundamental solution in micropolar thermoelastic materials with double porosity - Kumar, R.; Vohra, R.; Gorla, M.G. (Archives of Mechanics, 2016)
This paper is concerned with micropolar thermoelastic materials which have a double porosity structure. The system of the equations of the assumed model is based on the equations of motion, equilibrated stress equations of motion and heat conduction equation for material with double porosity. The explicit expressions for the fundamental solution of the system of equations in the case of steady vibrations are presented. The desired solutions are obtained by the use of elementary functions. Some basic properties are also established.